Implementasi Game Quizizz Sebagai Media Evaluasi Pembelajaran Daring Menyenangkan Di Masa Pandemi Covid-19 - Saiful Bahri; Abdul Mutaleb; Taufik Gunawan; Zamzami Zainuddin (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2021)
This study aims to recognize the effectiveness of the game Quizizz implementation in the learning process during the Covid-19 pandemic in the Public Service Management course at the National College of Administrative Sciences, Indonesia. Mixed-method research was employed in collecting the data from students during one semester of the teaching-learning period. Quantitative data were acquired from the results of the “Quizizz”-based assessment (midterm-test) and the final assessment which were analyzed using a t-test. Other quantitative data sourced were derived from questionnaires. These data analyzed students' thoughts and experiences of the advantage of the two applications "Quizizz" and "Padlet". For qualitative data, the data were obtained from the results of interviews with several students at the end of the semester. The results of the study indicated that the employment of the "Quizizz" game quiz application has a positive impact on student motivation and learning achievement in online classes during the Covid-19 pandemic. Teaching and learning activities become more interactive, innovative, fun, and not rigid and/or boring. Students in the class not only listen to lecturers' talks through the Zoom application but also interact with both lecturers and fellow students through the game activities. The employment of Quizizz game-based assessments could help instructors designed engaging content and entertained students in the learning process.